High-pressure experiments on a natural olivine gabbro from ODP Hole 176-735B - G M Yaxley; Alexander V Sobolev (PANGAEA, 2007)
We have conducted high-pressure experiments on a natural oceanic gabbro composition (Gb108). Our aim was to test recent proposals that Sr-enrichment in rare primitive melt inclusions from Mauna Loa, Hawaii, may have resulted from melting of garnet pyroxenite formed in the magma source regions by reaction of peridotite with siliceous, Sr-enriched partial melts of eclogite of gabbroic composition. Gb108 is a natural, Sr-enriched olivine gabbro, which has a strong positive Sr anomaly superimposed on an overall depleted incompatible trace element pattern, reflecting its origin as a plagioclase-rich cumulate. At high pressures it crystallises as a coesite eclogite assemblage, with the solidus between 1,300 and 1,350°C at 3.5 GPa and 1,450 and 1,500°C at 4.5 GPa. Clinopyroxenes contain 4-9% Ca-eskolaite component, which varies systematically with pressure and temperature. Garnets are almandine and grossular-rich. Low degree partial melts are highly siliceous in composition, resembling dacites. Coesite is eliminated between 50 and 100°C above the solidus. The whole-rock Sr-enrichment is primarily hosted by clinopyroxene. This phase dominates the mode (>75 wt%) at all investigated PT conditions, and is the major contributor to partial melts of this eclogite composition. Hence the partial melts have trace element patterns sub-parallel to those of clinopyroxene with ~10* greater overall abundances and with strong positive Sr anomalies. Recent studies of primitive Hawaiian volcanics have suggested the incorporation into their source regions of eclogite, formerly gabbroic material recycled through the mantle at subduction zones. The models suggest that formerly gabbroic material, present as eclogite in the Hawaiian plume, partially melted earlier than surrounding peridotite (i.e. at higher pressure) because of the lower solidus temperature of eclogite compared with peridotite. This produced highly siliceous melts which reacted with surrounding peridotite producing hybrid pyroxene + garnet lithologies. The Sr-enriched nature of the formerly plagioclase-rich gabbro was present in the siliceous partial melts, as demonstrated by these experiments, and was transferred to the reactive pyroxenite. These in turn partially melted, producing Sr-enriched picritic liquids which mixed with normal picritic partial melts of peridotite before eruption. On rare occasions these mixed, relatively Sr-rich melts were trapped as melt inclusions in primitive olivine phenocrysts.Yaxley-Sobolev
Supplement to: Yaxley, GM; Sobolev, AV (2007): High-pressure partial melting of gabbro and its role in the Hawaiian magma source. Contributions to Mineralogy and Petrology, 154(4), 371-383, https://doi.org/10.1007/s00410-007-0198-4